2018
DOI: 10.1136/bmjopen-2017-018391
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of coronary artery calcification in a non-specific chest pain population in emergency and cardiology departments compared with the background population: a prospective cohort study in Southern Denmark with 12-month follow-up of cardiac endpoints

Abstract: ObjectivesTo examine and compare the prevalence of coronary artery calcification (CAC) and the frequency of cardiac events in a background population and a cohort of patients with non-specific chest pain (NSCP) who present to an emergency or cardiology department and are discharged without an obvious reason for their symptom.DesignA double-blinded, prospective, observational cohort study that measures both CT-determined CAC scores and cardiac events after 1 year of follow-up.SettingEmergency and cardiology dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…More than 24,000 cardiac computed tomography (CT) scans were performed between 2007 and 2017 as part of clinical examinations at Odense University Hospital, or as part of research studies at five centres (Odense, Svendborg, Vejle, Esbjerg, Silkeborg). After approval from the Danish Data Protection Agency, traditional cardiovascular risk factors and CAC scores were collected from the electronic patient databases at Odense University Hospital, the Western Denmark Heart Registry [ 12 ], The National Danish Ablation Database [ 13 ], and research databases (DANCAVAS [ 14 ], DanRisk [ 15 ], IDA [ 16 ], MYODAN [ 17 ], NOTICE [ 18 ], AMFAST [ 19 ], and Ilangkovan N et al [ 20 ].). The study participants’ medication status since 2004 was collected from the Danish National Health Service Prescription Database (DNHSPD) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 24,000 cardiac computed tomography (CT) scans were performed between 2007 and 2017 as part of clinical examinations at Odense University Hospital, or as part of research studies at five centres (Odense, Svendborg, Vejle, Esbjerg, Silkeborg). After approval from the Danish Data Protection Agency, traditional cardiovascular risk factors and CAC scores were collected from the electronic patient databases at Odense University Hospital, the Western Denmark Heart Registry [ 12 ], The National Danish Ablation Database [ 13 ], and research databases (DANCAVAS [ 14 ], DanRisk [ 15 ], IDA [ 16 ], MYODAN [ 17 ], NOTICE [ 18 ], AMFAST [ 19 ], and Ilangkovan N et al [ 20 ].). The study participants’ medication status since 2004 was collected from the Danish National Health Service Prescription Database (DNHSPD) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ablation Database [13], and research databases (DANCAVAS [14], DanRisk [15], IDA [16], MYODAN [17], NOTICE [18], AMFAST [19], and Ilangkovan N et al [20].). The study participants' medication status since 2004 was collected from the Danish National Health Service Prescription Database (DNHSPD) [21].…”
Section: Plos Onementioning
confidence: 99%
“…No wonder, therefore, that arterial NaF-PET imaging, initiated in 2010 by Derlin et al who started looking at the prevalence and topographic distribution of NaF uptake compared to CT calcification in major arteries, 13,14 sparked an interest in studying NaF uptake in vulnerable coronary and carotid plaques [15][16][17][18] to achieve improved plaque characterization, since CT-calcification could not characterize the individual patient very precisely. [19][20][21] Post-mortem studies of patients dying from cardiac arrest and acute MI have indicated that the percent luminal area stenosis at sites of thrombus or at likely culprit lesions causing MI is very high (≥75%) and that only 10% of culprit lesions had a diameter of <50% after thrombosis removal. [22][23][24] In the heart, it is a limitation that even advanced approaches examine plaques exclusively in the proximal parts of the coronary tree 25,26 disregarding calcification in the distal and transmural branches supplying the subendocardial myocardial layers, where ischemia is more likely to trigger infarction and neuralgia.…”
Section: Atherosclerotic Disease Burden or Vulnerable Plaquementioning
confidence: 99%